THE READINESS OF KAMPUNG WISATA DANGEAN AS A RURAL TOURISM IN THE FOREIGN TOURIST'S PERSPECTIVE - Grendo Sigarete, Bayu; Ahmad, Halim; Nelindya Afriana, Ferita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2019)
Boyolali district is identical with dairy. Dangean village is located in the District of Cepogo which is a milk producing center in Boyolali. The majority of Dangean people as dairy farmers. The efforts to diversify the community business are by packing the daily activities of residents as a breeder to serve as a tourist attraction in rural tourism. This research is a descriptive qualitative research. The method that is used in this research is experiment. The sample determination is done by purposive method that is foreign student representing foreign tourists. The sample is 5 foreign students. The number of samples is determined by considering the readiness of the facilities currently available in Dangean. The results of research conducted by a team of researchers from Ambarrukmo Tourism institute (STIPRAM) Yogyakarta showed that the attractions and packaging tour packages are the factors that become the main preference tourists when traveling in Dangean. The main strengths of Dangean are the activity of attractiveness, the visual landscape of the area, and the package of tourism activities. While the weakness that is currently owned by Dangean is the low level of popularity, competitiveness, and service.Keywords: Dangean Village, Kampung Wisata, attractions, tour packages.